Correlations of serum uric acid, fibrinogen and homocysteine levels with carotid atherosclerosis in hypertensive patients - Zhang, Liling; Lu, Shenlu; Guo, Juanjuan (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveUric acid (UA), fibrinogen (FIB), and homocysteine (Hcy) are the main contributors to cardiovascular and cerebrovascular diseases, and are related to hypertension. Hypertension plays a role in atherosclerosis (CAS). We hence explored the correlations of UA, FIB, and Hcy levels with CAS in hypertensive patients.MethodsTotally 170 hypertensive patients were retrospectively included and assigned into the Non-sclerosis, Thickened, and Plaque groups based on carotid intima-media thickness (cIMT), with serum UA, FIB, and Hcy compared. Correlations of UA, FIB, and Hcy with cIMT and carotid atherosclerotic plaque (CAP) were assessed using Spearman's correlation analysis. The risk factors of CAS were evaluated by logistic multivariate regression analysis. The predictive value of UA, FIB, and Hcy for CAS was estimated by the receiver operating characteristic (ROC) curve.ResultsUA, FIB, and Hcy were up-regulated in the Plaque group vs. other two groups. Serum UA, FIB, and Hcy were positively linked to cIMT and CAP, and were independent risk factors for CAS. The area under ROC curve of UA, FIB, Hcy levels and their combination for predicting CAS were 0.889, 0.855, 0.902, and 0.958, respectively. Hypertensive patients with high levels of UA, FIB, or Hcy were more likely to develop CAS.ConclusionSerum UA, FIB, and Hcy are positively correlated with cIMT and CAP, and are independent risk factors for CAS in hypertensive patients. High UA, FIB and Hcy expression could assist in predicting CAS in patients with hypertension, and the combination of the three was more valuable than all three alone.